2010
DOI: 10.3390/cancers2020338
|View full text |Cite
|
Sign up to set email alerts
|

The "Two-Faced" Effects of Reactive Oxygen Species and the Lipid Peroxidation Product 4-Hydroxynonenal in the Hallmarks of Cancer

Abstract: Reacytive Oxygen Species (ROS) have long been considered to be involved in the initiation, progression and metastasis of cancer. However, accumulating evidence points to the benefical role of ROS. Moreover, ROS production, leading to apoptosis, is the mechanism by which many chemotherapeutic agents can act. Beside direct actions, ROS elicit lipid peroxidation, leading to the production of 4-hydroxynoneal (HNE). Interestingly, HNE also seems to have a dual behaviour with respect to cancer. In this review we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 180 publications
1
63
0
1
Order By: Relevance
“…It is now well known that many cancer cells possess higher cellular oxidative stress with increased levels of ROS than normal cells (23,24). We have also demonstrated that ROS levels in androgen-sensitive LNCaP prostate cancer cells or androgeninsensitive DU-145 prostate cancer cells could be further modulated by selected androgen (26,27) or polyamine analogs (28, 29), respectively, as well as polyamine oxidase inhibitors (30).…”
Section: Lnm E1 (2) Showing Potent Cytotoxicity Against Prostate Cancmentioning
confidence: 64%
See 1 more Smart Citation
“…It is now well known that many cancer cells possess higher cellular oxidative stress with increased levels of ROS than normal cells (23,24). We have also demonstrated that ROS levels in androgen-sensitive LNCaP prostate cancer cells or androgeninsensitive DU-145 prostate cancer cells could be further modulated by selected androgen (26,27) or polyamine analogs (28, 29), respectively, as well as polyamine oxidase inhibitors (30).…”
Section: Lnm E1 (2) Showing Potent Cytotoxicity Against Prostate Cancmentioning
confidence: 64%
“…The feasibility of exploiting 2 as an anticancer prodrug activated by ROS was demonstrated in two prostate cancer cell lines, LNCaP and DU-145, that are known to exist under higher oxidative stress than normal tissues. Because many cancer cells are under higher cellular oxidative stress with increased levels of ROS than normal cells (23,24), our results suggest a means of exploiting ROS to target cancer cells and highlight 2 as a novel lead for the development of anticancer prodrugs activated by ROS.…”
Section: Significancementioning
confidence: 88%
“…In the membranes of cells, ROS target polyunsaturated fatty acids and initiate lipid peroxidation. Malonaldehyde (MDA) is a major end product from the peroxidation of lipid membranes and used for the assessment of damage by ROS (Pizzimenti et al 2010;Siddique et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among the products of LPO, 4-hydroxy-2-alkenals represent the most biologically active alkenals and aldehydes, that, due to their prolonged half-lives and their ability to diffuse from their sites of formation, have been considered as second messengers of oxidative stress (14). The peroxidation of n-3 polyunsaturated fatty acids (Ī±-linolenic acid and docosahexaenoic acid) generates 4-hydroxy-hexenal (HHE), which is a mediator of the mitochondrial permeability transition (99), while the peroxidation of n-6 polyunsaturated fatty acids, such as linoleic acid and arachidonic acid, generates 4-hydroxy-2-nonenal (HNE), which is the most intensively studied aldehyde (15,154), because it is highly electrophilic and easily reacts with low-molecular-weight compounds, such as glutathione (GSH), with proteins and, at higher concentrations, with DNA (57,204). The mechanism of HNE formation during peroxidation of arachidonic acid is reported in Fig.…”
Section: Introductionmentioning
confidence: 99%